Genetic and nongenetic variation in plasma and milk β-hydroxybutyrate and milk acetone concentrations of early-lactation dairy cows - van der Drift, S G A; van Hulzen, K J E; Teweldemedhn, T G; Jorritsma, R; Nielen, M; Heuven, H C M (Elsevier Inc., 2012)
This study assessed genetic variation, heritability estimates, and genetic correlations for concentrations of plasma β-hydroxybutyrate (BHBA), milk BHBA, and milk acetone in early lactation to investigate differences between cows in susceptibility to hyperketonemia and possibilities to use test-day milk ketone bodies for genetic improvement. Blood and test-day milk samples were collected on randomly selected dairy farms in the Netherlands from cows of various parities between 5 and 60 d in milk. Plasma samples were analyzed for BHBA (reference test for hyperketonemia) and test-day milk samples were analyzed for BHBA and acetone using Fourier-transform infrared spectroscopy. The final data set consisted of plasma BHBA concentrations of 1,615 cows from 122 herds. Milk BHBA and milk acetone concentrations were determined for 1,565 cows. Genetic variation, heritability, and proportion of phenotypic variation attributable to the herd were estimated using an animal model with fixed effects for parity and season, a covariate for days in milk, and random effects for herd, animal, and error. Genetic correlations for plasma BHBA, milk BHBA, and milk acetone were estimated using bivariate analyses. The heritability estimate for plasma BHBA concentrations in early lactation was 0.17, whereas heritability estimates for milk BHBA and milk acetone were 0.16 and 0.10, respectively. This indicates that selective breeding may contribute to a lower incidence of hyperketonemia in early lactation. For the 3 traits, the proportion of variance attributable to herd was larger than the additive genetic variance, underlining the importance of on-farm feeding and management in the etiology of hyperketonemia in fresh cows. Prevention strategies for hyperketonemia can, therefore, include both feeding and management strategies at dairy farms (short-term) and genetic improvement through breeding programs (long-term). Genetic correlations between concentrations of plasma BHBA and milk BHBA (0.52) or milk acetone (0.52) were moderate. As milk ketone bodies can be routinely analyzed at test days, this may provide a practical alternative for breeding programs aimed at reducing hyperketonemia in early lactation.
Keywords: 3-Hydroxybutyric Acid; Acetone; Animals; Cattle; Cattle Diseases; Female; Genetic Variation; Ketosis; Lactation; Milk; Phenotype; Quantitative Trait, Heritable